Efficacy, Environmental Persistence of Chlorantraniliprole 50%w/w FS (625g/L) Seed Treatment Against Yellow Stem Borer, Scirpophaga incertulas Walker and its Safety to Natural Enemies in Direct Seeded Rice in Indo Gangetic Plain: Chlorantraniliprole seed treatment against rice yellow stem borer - Maha Singh Jaglan; O.P. Chaudhary; Chitralekha; Sushil Ahlawat; Vijay Kumar; Rajan, Rajan Kamboj (Journal of Cereal Research, 2025)
The increasing popularity of direct seeded rice could be attributed to various benefits, including reduced labor costs, reduced water requirement, lower production cost, improved soil physical conditions and reduced methane emissions. It also provide a better option to fit in different cropping system. Yellow stem borer, Scirpophaga incertulas Walker causes considerable economic losses in India and is a dominant pest among the rice insect pests. The first line of defense against insect-pests is chemical control measures. However, because of the development of insecticide resistance, managing insect-pests has become more challenging. Among the different insecticides used against S. incertulas in rice has not effectively controlled this pest. Seed treatment is the most significant application mode for insecticides. Seed treatment requires much less pesticide than broadcast or spray, which also ensures no threats to human health or the environment. In this direction, a novel molecule i.e., chlorantraniliprole 625g/L FS as seed treatment was evaluated for the management of S. incertulas in direct seeded rice. The present research findings indicate that during the two study years, the most effective and best insecticidal treatment for minimizing S. incertulas damage proved to treat the seeds with chlorantraniliprole 625g/L FS @ 75 g a.i. ha-1 or 3.75 g a.i. kg-1 seed. This resulted in increased grain yield in both experimental seasons. Seed treatment with chlorantraniliprole 625g/L FS did not cause any phytotoxicity symptoms in the rice crop even at a high dose of 180 g a.i. ha-1. On a 0–10 scale, phytotoxicity was rated as 0, indicating the crop is completely safe. All doses of chlorantraniliprole 625g/L FS (67.5, 75.0, 82.5, and 90.0 g a.i. ha-1) were also proven to be harmless for natural enemies, such as mirid bugs, coccinellid beetles and spiders. During the 2019 and 2020 crop seasons, the maximum grain yield (42.05 & 40.21 q ha-1) was reported in the seed treatment with chlorantraniliprole 625g/L FS @ 90.0 g a.i ha-1, which was comparable to 82.5 & 75.0 g a.i. ha-1. The residues of chlorantraniliprole 625g/L FS @ 75.0 g a.i. ha-1 and 150 g a.i.ha-1 analyzed were below the quantification limit of 0.01 mg kg-1 in field soil, grain and paddy straw at harvest.